Nonpharmacologic Pain Management and Muscle Strengthening following Total Knee Arthroplasty - Chughtai, Morad; Elmallah, Randa D. K.; Mistry, Jaydev B.; Bhave, Anil; Cherian, Jeffrey Jai; McGinn, Tanner L.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2016)
Despite technological advances in total knee arthroplasty (TKA), management of postoperative muscle weakness and pain continue to pose challenges for both patients and health care providers. Nonpharmacologic therapies, such as neuromodulation in the form of neuromuscular electrical stimulation (NMES) and transcutaneous electrical nerve stimulation (TENS), and other modalities, such as cryotherapy and prehabilitation, have been highlighted as possible adjuncts to standard-of-care pharmacologic management to treat postoperative pain and muscle weakness. The aim of this review was to discuss existing evidence for neuromodulation in the treatment of pain and muscular weakness following TKA, and to shed light on other noninvasive and potential future modalities. Our review of the literature demonstrated that NMES, prehabilitation, and some specialized exercises are beneficial for postoperative muscle weakness, and TENS, cooling therapies, and compression may help to alleviate post-TKA pain. However, there are no clear guidelines for the use of these modalities. Further studies should be aimed at developing guidelines or delineating indications for neuromodulation and other nonpharmacologic therapies in the management of post-TKA pain and muscle weakness.
Keywords: pain management; total knee arthroplasty; strengthening; nonpharmacologic